The transseptal puncture experience: Safety insights from FDA MAUDE database. Issue 6 (1st May 2021) - Morcos, Ramez; Megaly, Michael; Desai, Anand; Alkhouli, Mohamed; Saad, Marwan; Luna, Michael; Garcia, Santiago; Khalili, Houman; Maini, Brijeshwar
Abstract: Background: There is a paucity of literature on safety and efficacy of various transseptal puncture (TSP) needles. Objectives: To assess the reported mechanisms of failure, complications, and outcomes among the most frequently used transseptal needles in the United States. Methods: We queried the Food and Drug Administration (FDA) Manufacturer and User Facility Device Experience (MAUDE) database between January 2011 and January 2021 for reports on the most commonly used transseptal needles: NRG (Baylis Medical, Montreal, Canada), and BRK (St. Jude, Saint Paul, MN)]. The primary outcome was the mechanism of failure. Secondary outcomes included clinical consequences of device failure. Results: The final analysis included 306 reports of failure/complication with TSP needles (NRG n  = 70, BRK n  = 236). The most commonly reported mode of failure was detachment of the needle component (i.e., clip, hub, stopcock, shaft, spring, or needle tip) (14.7% overall; 17.8% BRK; and 4.3% NRG). Among these reports, cardiac perforation was the most common complication (69.9% overall; 69.1% for BRK; and 72.9% for NRG). Pericardiocentesis was the second most commonly reported complication (45.1% overall; 48.3% for BRK; and 34.3% for NRG). The procedure was successfully completed in 33.3% of all cases (36.4% for BRK and 22.9% for NRG), while surgical conversion was needed in (13.4% overall; 14% for BRK and 11.4% for NRG) of the reports. Death occurred in 3.9% of all cases overall (3.4% for BRK and 5.7% for NRG). Conclusions: Needle detachment was the most common mode of failure, and cardiac perforation was the most common complication reported with TSP needles. Future efforts should focus on innovative TSP needle design, best practice guidelines, including role of imaging guidance, and increased TSP training.